El juego y la motricidad gruesa en los niños de 4 a 5 años del centro de educación inicial particular los Olivos ubicado en la ciudad de Loja, período 2019-2020. - Quezada Sánchez, María Luisa (2021)
The present research work entitled: GAME AND GROSS MOTOR IN CHILDREN FROM 4 TO 5 YEARS OLD FROM THE LOS OLIVOS PARTICULAR INITIAL EDUCATION CENTER LOCATED IN THE CITY OF LOJA, PERIOD 2019-2020. Its general objective was: Analyze the importance of games in children's gross motor skills. The research was non-experimental, since I do not know how to manipulate or experiment with the current object of study. For the development of the research, the methods were used: analytical, synthetic, descriptive, deductive and inductive, the instruments for obtaining information were: the same survey that was applied to 2 teachers of the Educational Institution and the Scale of Development of Nelson Ortiz applied to 13 children from the aforementioned institution, through which it was shown that 62% of the children evaluated have difficulties in the gross motor area, developing problems performing activities of daily living such as running, jumping, throwing and catching the ball, walking backwards, standing on one foot, among others; in the same way problems in attention and concentration. Given this, it is concluded that it is vitally important to continuously stimulate gross motor skills through didactic strategies according to the need and age of each child, in order to obtain significant learning, which is the support for their normal development.